Value chain and stakeholders’ analyses of batik tulis industry in Indonesia - Isa, Muzakar; Wajdi, M. Farid; Mangifera, Liana; Mardalis, Ahmad; Kamarulzaman, Nitty Hirawaty (Universitat de Barcelona, Facultad de Economia y Empresa, 2023)
The study aims to analyze the values added of batik tulis production and to analyze stakeholders’ objectives and competitiveness of batik tulis business. The study used a mixed method, a combination of quantitative and qualitative analysis. The data were analyzed using several analyses namely content analysis, value chain analysis, and stakeholder analysis. The content analysis was carried out to identify and to explain the supply chain of batik tulis production. The value chain analysis was undertaken to identify the existing stages of the value chain in batik tulis production. The stakeholders analysis was used to analyze stakeholders’ objectives and competitiveness of batik tulis business. The results revealed that the value chain of batik tulis production started from the procurement of raw materials, production processes, and sales. The highest added values obtained were through sales to wholesalers and retailers as compared to sales by displaying the products in galleries. The average profit margin earned by each entrepreneur exceeded 50% of the main production costs. Profit and reputation were revealed as the two stakeholders’ objectives that have the strongest and the most dominant influences in the industry. The entrepreneurs are expected to further optimize the activities that contribute the highest added values to be more efficient in managing the production costs, and in maintaining the interrelationship with other players of batik tulis entrepreneurs as well as with the suppliers of raw materials so that the cooperation can be carried out effectively.